2021
DOI: 10.1039/d0sm01670e
|View full text |Cite
|
Sign up to set email alerts
|

Gauge invariant and gauge dependent aspects of topological walking colloidal bipeds

Abstract: Paramagnetic colloidal spheres assemble to colloidal bipeds of various length in an external magnetic field and walk on a magnetic pattern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Experimental setup. In previous work, we have shown that topologically nontrivial transport appears in colloidal [44][45][46][47][48][49][50][51] and in macroscopic 52,53 magnetic particle systems that are subject to dissipative dynamics. Here, we use macroscopic magnetic particles immersed in water to drive these particles through the magnetic potential created between two shifted and oppositely rotated magnetic square patterns.…”
Section: Resultsmentioning
confidence: 97%
“…Experimental setup. In previous work, we have shown that topologically nontrivial transport appears in colloidal [44][45][46][47][48][49][50][51] and in macroscopic 52,53 magnetic particle systems that are subject to dissipative dynamics. Here, we use macroscopic magnetic particles immersed in water to drive these particles through the magnetic potential created between two shifted and oppositely rotated magnetic square patterns.…”
Section: Resultsmentioning
confidence: 97%
“…In our metamorphic pattern, the symmetry phase varies with the location on the pattern, and this allows us to use well-designed loops where single colloids are transported in different directions in different regions of the metamorphic pattern 13 . Colloidal bipeds formed by several particles can also be transported 8 , 14 . The biped aligns with the external field since dipolar interactions are stronger than the buoyancy.…”
Section: Resultsmentioning
confidence: 99%
“…As a result the bipeds actively walk by alternatingly grounding one of their feet. In addition, as for the single colloids, the grounded foot passively slides above the pattern 8 , 14 , 15 .…”
Section: Resultsmentioning
confidence: 99%